EFFECT OF SOIL pH AND TEMPERATURE ON SEEDLING MORTALITY OF GUAR CAUSED BY SCLEROTIUM ROLFSll AND ITS FUNGICIDAL CONTROL - S. K. GANDHI, R. P. SINGH AND (Indian Phytopathology, 2002)
Sclerotium rollsii caused maximum seedling mortality in guar at pH 6.1 and increased pH from 6.1 to 8.4 significantly reduced the disease incidence. Efficacy of all the four fungicides used as seed treatment V’’§ also affected by soil pH at 6.1, it was significantly reduced, while at 6:8 and 7.5, no significant differences were observed. In untreated set, the disease incidence was 100 per cent at 30Â°C, while at 25 and 35Â°C, seedling mortality was 95 and 83 per cent, respectively. Efficacy of rizolex and vitavax was significantly less at 30Â°C, but disease controlling potential of both difolatan and thiram was not affected by temperature.